2015
DOI: 10.2298/mpns1504122h
|View full text |Cite
|
Sign up to set email alerts
|

Chikungunya - a serious threat for public health

Abstract: Fast developing international traffic and booming tourism as well as the vector spreading from its homeland make chikungunya a real threat to our country.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
6
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 13 publications
0
6
0
Order By: Relevance
“…Mosquito-borne arboviruses constitute an important proportion of emerging infectious diseases that are a global threat to the human and animal populations [1–5]. About 167/300 (55.7 %) of the viruses in ‘The Arthropod-borne viruses of vertebrates’, a book that gives an account of the activities of the Rockefeller Foundation program were listed as transmitted by mosquitoes [6].…”
Section: Introductionmentioning
confidence: 99%
“…Mosquito-borne arboviruses constitute an important proportion of emerging infectious diseases that are a global threat to the human and animal populations [1–5]. About 167/300 (55.7 %) of the viruses in ‘The Arthropod-borne viruses of vertebrates’, a book that gives an account of the activities of the Rockefeller Foundation program were listed as transmitted by mosquitoes [6].…”
Section: Introductionmentioning
confidence: 99%
“…Chikungunya, a Makonde term meaning "that which bends up" [23], is an acute illness similar to dengue that is characterized by the abrupt onset of high-grade fever, followed by constitutional symptoms such as polyarthritis, musculoskeletal pain, headache, and skin involvement [24], and in rare cases by severe manifestations such as encephalopathy [21,24], acute hepatitis [25,26], myocarditis [27][28][29], and multi-organ failure. The acute phase (viremic period) lasts from 5 to 10 days on average, and is resolved within a few weeks.…”
Section: Introductionmentioning
confidence: 99%
“…Female Aedes aegypti mosquitoes are responsible for the propagation of diseases of public health significance: yellow fever, dengue, chikungunya, and Zika virus (1)(2)(3)(4)(5)(6). The unfortunate convergence of a lack of vaccines for dengue, chikungunya, and Zika viruses, the increase of global disease distribution due to climate change (7)(8)(9), and an increase in travel clearly demand better mosquito vector control strategies.…”
mentioning
confidence: 99%
“…During blood meal digestion, only a small percentage of amino acids is retained for follicle development and maternal reserves, whereas the majority of amino acids are oxidized for metabolic needs and excreted as CO 2 or other waste (10,11). One of the by-products of blood digestion is ammonia, defined here as NH 3 , NH 4 + , or a combination of both. Previous studies have demonstrated that Ae.…”
mentioning
confidence: 99%